2014
DOI: 10.1063/1.4901060
|View full text |Cite
|
Sign up to set email alerts
|

Important role of the non-uniform Fe distribution for the ferromagnetism in group-IV-based ferromagnetic semiconductor GeFe

Abstract: We investigate the growth-temperature dependence of the properties of the group-IV-based ferromagnetic semiconductor Ge1−xFex films (x = 6.5% and 10.5%), and reveal the correlation of the magnetic properties with the lattice constant, Curie temperature (TC), non-uniformity of Fe atoms, stacking-fault defects, and Fe-atom locations. While TC strongly depends on the growth temperature, we find a universal relationship between TC and the lattice constant, which does not depend on the Fe content x. By using the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 36 publications
(32 reference statements)
1
30
1
Order By: Relevance
“…The value of ∼0.2 eV is smaller than the experimental value of 0.35 eV. This is probably due to the existence of ∼15% of interstitial Fe atoms [12], which provide two electrons per Fe atom to the sp orbitals and partially compensates holes. Figure 3(b) shows the spin-averaged PDOS of Fe 3d(t 2 ) and 3d(e) orbitals in comparison with the experimentally obtained PDOS.…”
contrasting
confidence: 44%
See 3 more Smart Citations
“…The value of ∼0.2 eV is smaller than the experimental value of 0.35 eV. This is probably due to the existence of ∼15% of interstitial Fe atoms [12], which provide two electrons per Fe atom to the sp orbitals and partially compensates holes. Figure 3(b) shows the spin-averaged PDOS of Fe 3d(t 2 ) and 3d(e) orbitals in comparison with the experimentally obtained PDOS.…”
contrasting
confidence: 44%
“…Group-IV FMSs are particularly important because they are compatible with mature Si-based technology. Ge 1−x Fe x (Ge:Fe) is a promising material [9][10][11][12], and indeed can be grown epitaxially on Ge and Si substrates by the low-temperature molecular beam epitaxy (LT-MBE) method without the formation of intermetallic precipitates [13]. It shows p-type conduction, but the carrier concentration of ∼10 18 cm −3 [13] is orders of magnitude smaller than that of doped Fe atoms (∼10 21 cm −3 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In either case, the magnitude of T (app) C correlates with the nonuniformity of the Fe distribution and the stacking fault density (Wakabayashi et al, 2014a,b). Meanwhile, channeling Rutherford backscattering and particle-induced x-ray emission measurements revealed that about 15% of the Fe atoms reside in the tetrahedral interstitial sites and that the substitutional Fe concentration, in agreement with the decomposition scenario, is barely correlated with the magnitude of T (app) C (Wakabayashi et al, 2014b). At the same time, all the (Ge,Fe) films show a weak spin-glasslike behavior in a low-temperature region (below ∼ 26 K), which is insensitive to the annealing temperature.…”
Section: Structural and Chemical Characterizationmentioning
confidence: 83%